The modernization of the Western world a society transformed - McGrath, John T. 1956-; Martin, Kathleen Callanan 1949-; Corrin, Jay P.; Kort, Michael G.; Lee, Susan Hagood; Mackey, John W.; Varat, Benjamin E. (Routledge, 2017)
"Presents an overview of the history of Western civilization from ancient history to the current era of globalization"-- Provided by publisher.